DNA Repair Deficiency in Neurodegeneration - Jeppesen, Dennis Kjølhede (2011)
Deficiency in repair of nuclear and mitochondrial DNA damage has been linked to several neurodegenerative disorders. Many recent experimental results indicate that the post-mitotic neurons are particularly prone to accumulation of unrepaired DNA lesions potentially leading to progressive neurodegeneration. Nucleotide excision repair is the cellular pathway responsible for removing helix-distorting DNA damage and deficiency in such repair is found in a number of diseases with neurodegenerative phenotypes, including Xeroderma Pigmentosum and Cockayne syndrome. The main pathway for repairing oxidative base lesions is base excision repair, and such repair is crucial for neurons given their high rates of oxygen metabolism. Mismatch repair corrects base mispairs generated during replication and evidence indicates that oxidative DNA damage can cause this pathway to expand trinucleotide repeats, thereby causing Huntington’s disease. Single-strand breaks are common DNA lesions and are associated with the neurodegenerative diseases, ataxia-oculomotor apraxia-1 and spinocerebellar ataxia with axonal neuropathy-1. DNA double-strand breaks are toxic lesions and two main pathways exist for their repair: homologous recombination and non-homologous end-joining. Ataxia telangiectasia and related disorders with defects in these pathways illustrate that such defects can lead to early childhood neurodegeneration. Aging is a risk factor for neurodegeneration and accumulation of oxidative mitochondrial DNA damage may be linked with the age-associated neurodegenerative disorders Alzheimer’s disease, Parkinson’s disease and amyotrophic lateral sclerosis. Mutation in the WRN protein leads to the premature aging disease Werner syndrome, a disorder that features neurodegeneration. In this article we review the evidence linking deficiencies in the DNA repair pathways with neurodegeneration.